2019
DOI: 10.1016/j.watres.2019.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of media coating on simultaneous manganese removal and remineralization of soft water via calcite contactor

Abstract: The aim of this study was to investigate the negative impact of a newly-formed manganese (Mn)layer on calcite dissolution in the long-term operation of a calcite contactor. Simultaneous removal of Mn and remineralization of soft water in an up-flow calcite contactor was conducted and led to a progressive loading of Mn into the calcite matrix. The calcite contactor demonstrated high Mn removal; however, the hardness release decreased from 32 to 20 mg CaCO3 L -1 after 600 h of operation on a high Mn concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…They justified this mechanism by the quantitative measurement of the molar amount of Mg 2+ released and the amount of Pb 2+ or Cd 2+ adsorbed in batch experiments, finding a linear relationship [79]. While we were not able to find any other work investigating metal removal by cation exchange for MgO, previous research has found that calcite effectively removes Me 2+ from solution by such a mechanism [76].…”
Section: Cation Exchangesupporting
confidence: 58%
See 4 more Smart Citations
“…They justified this mechanism by the quantitative measurement of the molar amount of Mg 2+ released and the amount of Pb 2+ or Cd 2+ adsorbed in batch experiments, finding a linear relationship [79]. While we were not able to find any other work investigating metal removal by cation exchange for MgO, previous research has found that calcite effectively removes Me 2+ from solution by such a mechanism [76].…”
Section: Cation Exchangesupporting
confidence: 58%
“…In a water treatment context, the interaction of dissolved metals with a mineral surface becomes interesting if it leads to the retention of the metal. Using calcite for the remineralization and simultaneous removal of manganese from synthetic feedwater, Pourahmad and co-workers found that the media was progressively loaded with a stable MnO x film [76]. The authors proposed that, upon initial removal as MnCO 3 through an ionexchange sorption reaction, the metal carbonate slowly recrystallizes as MnO 2 .…”
Section: Presence Of Dissolved Metalsmentioning
confidence: 99%
See 3 more Smart Citations